Quantum degeneracy and white dwarfs - Moriconi, Marco; Negreiros, Rodrigo (Cadernos de Astronomia, 2025)
White dwarfs are highly compact stellar remnants resulting from the evolutionary process of stars with masses up to ten times that of our Sun. Their core is composed predominantly of electronically degenerate matter. In an ordinary star, there is a balance between the intrinsic gravitational attraction and the internal pressure generated by the heat and nuclear radiation from its core. In a white dwarf, collapse is prevented by the electron degeneracy pressure, a quantum effect that arises from the statistical properties of fermions through the Pauli exclusion principle. In this article, we present a simple theoretical model for the structure of white dwarfs and discuss some of its applications in astrophysics.
Keywords: White Dwarfs; Quantum Degeneracy